Microfading tests through glass: evaluation and recommendations. Issue 4 (21st April 2021) - Prestel, Thomas
Abstract: Lightfastness tests of cultural objects are performed with so-called microfading test systems. The system allows measurements through glass. Case studies showed that tests through glazing are feasible, but some theoretical and practical aspects are not clarified. In this paper, the influence of the glazing on the measurement is analyzed theoretically and experimentally. Deviations in the precision of color measurements through glass are analyzed. Furthermore, the lightfastness of samples is tested through glass and compared to tests without glass. Results indicate that lightfastness tests through glass are an awkward task, especially if tests with and without glass are compared. Recommendations for the execution and evaluation of tests through glass are given.